Management Assistance Of Cahaya Baru Art Studio as a Place to Develop The Children's Interest and Talent in Cahaya Baru Village, Jejangkit District of Batola - Jamiatul Hamidah; Muhammad Wira Wahyudi; Dina Rafidiyah (Comment: an International Journal of Community Development, 2020)
The advancement of technological development allows humans to be oriented to things that are easily accessible through digital media. It is also when looking for entertainment or free time. Considering their level of age, children are very susceptible to the negative impacts of technological sophistication. Those who should go through the phase of playing with activities to build creativity and innovative nature, in fact many who pass their days by playing online games or social media via smartphone/device. Concerned about this condition, we are cooperating with the first-generation students of Community Service Program students of Universitas Muhmmadiyah Banjarmasin (UMB), providing assistance to manage art, language, and literature studios in Cahaya Baru Village. The method of implementation is to provide training to children in the Cahaya Baru Village. Training in the form of reading poetry, singing, and staging drama (theater). The results of this activity show the enthusiasm of children to learn, develop interests and talents in the fields of art, language, and literature. In addition, children have a place to foster their creativity and fill their free time with positive and useful activities.